Fejér-type inequalities for strongly convex functions - Azócar, Antonio; Nikodem, Kazimierz; Roa, Gari (Annales Mathematicae Silesianae, 2013)
Fejér-type inequalities as well as some refinement and a discrete version of the Hermite–Hadamard inequalities for strongly convex functions are presented.